A Synoptic analogue model to issue QPF over Gangetic West Bengal and adjoining Jharkhand - CHATTOPADHYAY, S.; SENGUPTA, S. (MAUSAM, 2018)
In this study the Areal Average Precipitation (AAP) data for each day over each of the six catchments of Gangetic West Bengal (GWB) and adjoining Jharkhand namely river catchments of Mayurakhshi, Ajoy, Kansabati, Damodar, Barakar and Lower Valley of Damodar Valley Corporation during monsoon season for 25 years from 1990 to 2014 have been analyzed by grouping the AAP in three different ranges (11-25 mm, 26-50 mm, 51-100 mm and more), excluding Mainly Dry and 01-10 mm. The associated main synoptic features viz., trough at mean sea level, low pressure area, well marked low pressure area, cyclonic storm and cyclonic circulation for each day and their location with respect to the river catchments, viz., over the catchment, neighbourhood of the catchment (within 200 km South or North) and outside the catchment (more than 200 km South or North) have also been studied. The association of AAP ranges over six catchments with different categories of synoptic features has been examined. The distribution of percentage frequency of AAPs associated with the category of synoptic feature for the period 1990 to 2014 has led to development of a Synoptic Analogue Model (SAM) for issue of Quantitative Precipitation Forecast (QPF). The results obtained from SAM have been verified for rainfall data and calculated AAPs of monsoon season of 2015 over all the catchments and different skills scores also presented in this study.